EFISIENSI TEKNIS USAHATANI TEBU RAKYAT DENGAN PENDEKATAN STOCHASIC FRONTIER DI KABUPATEN LAMPUNG UTARA - Tri Novi Astuti; Fembriaty Erry Prasmatiwi; Ktut Murniati (Politeknik Negeri Lampung, 2021)
The objectives of this research were to find out the income of sugar cane farming, technical efficiency of sugar cane farming and determine the factors influencing the technical inefficiency of sugar cane farming in North Lampung Regency. The location was determined purposively, considering that North Lampung Regency has been the center of sugar cane production in Lampung Province. The number of respondents in this research were 35 respondents for plant cane (PC) criteria and 50 respondents for ratoon cane (RC) criteria, sampling was used by random sampling methods. Data were collected from February to March 2020. The analytical methods that used were farm income analysis and stochastic frontier approach. The study shows that the average income for total cost of sugar cane farming PC and RC criteria was Rp6.549.817,82/hectare and Rp13.547.014,64/hectare. Sugar cane farming in North Lampung Regency is technically efficient with a percentage of 96 percent and 91 percent for PC criteria and RC criteria, the factors that influence technical inefficiency in sugar cane farming was the level of farmer education and farmer participation in extension activities for PC criteria and for RC criteria was age and education level of farmers.